Is the ordinary administrative litigation process the best way to resolve legal conflicts in the public labor system and social security? - Corrales Melgarejo, Edwin Ricardo (2023)
The author considers that the ordinary administrative litigation process is not the best way to manage the controversies that relate to pensioners and workers of the public labor regime. Therefore, it proposes that, like the laudable restructuring in the civil justice system, based on the experience of the New Labor Procedure Law, the oral process by hearings be adopted through the intensive use of information and communication technologies, and that the competences of the recurring cases be redistributed, easy, less complex and amount, to the justices of the peace lawyer, taking into account the food nature of such claims and the urgency in their resolution, until our procedural system incorporates them legislatively.